Exploring the importance of innovation ambidexterity on performance: Insights from NCA and IPMA analysis - Martínez-Azúa, B. C.; Dias, Á.; Sama-Berrocal, C. (International Journal of Innovation Science, 2025)
Purpose – Agribusiness shows a growing degree of competitiveness and innovation. However, the organizational mechanisms that compete for innovation and organizational performance are not sufficiently studied. Thus, this study aims to analyze the influence of market orientation and organizational structure on innovation generated and its influence on market and financial performance in agribusiness firms in Extremadura (Spain). Design/methodology/approach – A conceptual model was designed and tested. Data were collected from a questionnaire sent to innovative agri-food companies. The analysis of the model methodologically combines Partial Least Square Structural Equation Modelling (PLS-SEM), Necessary Condition Analysis (NCA), and Importance-Performance Map Analysis (IPMA). Findings –The main results reveal that low levels of innovation ambidexterity impact significantly performance but when compared to exploitative innovation, explorative innovation shows a stronger influence on the market and financial performance. Practical implications –The results are intended to be useful to managers to improve their innovative performance by incorporating new strategies in the market orientation and organizational structure. Originality/value – The originality of this research lies in the novelty of the proposed mediators, as well as the sector under study. The study expands the knowledge of the influence that market orientation and organizational structure have on the types of innovation (exploitative/explorative).